Systematic revision of the Potamotrygon scobina Garman, 1913 species-complex (Chondrichthyes: Myliobatiformes: Potamotrygonidae), with the description of three new freshwater stingray species from Brazil and comments on their distribution and biogeography - Fontenelle, João Pedro; de Carvalho, Marcelo R. (Zootaxa, 2017)
Potamotrygon scobina Garman, 1913, described from Cametá, rio Tocantins, lower Amazon basin, is taxonomically reviewed through an extensive morphological study of internal and external features. Specimens identified as P. scobina from different locations of the Amazon basin were also studied. The identity of P. scobina, its morphology, and distribution are redefined. In addition, three new species closely related to P. scobina are described from Brazil: Potamotrygon adamastor, sp. nov., from rio Uraricoera, rio Branco system, upper Amazon basin; Potamotrygon amazona, sp. nov., from rio Juruá, upper Amazon basin; and Potamotrygon garmani, sp. nov., from the mid to upper rio Tocantins. These three new species do not occur sympatrically with P. scobina, as far as known. Together with P. scobina and P. limai Fontenelle, Silva & Carvalho, 2014, the new species have three angular cartilages of different sizes, a condition not seen in any other potamotrygonin (which have either one or two angulars). Diagnostic characters in combination are primarily morphometric proportions, especially tail length and width, dermal denticles and tail thorns (their relative size, number, morphology, and distribution), tooth size and number of rows, and color pattern. Printed copy of this book is available from US24.6 plus postage, Click here to order.